Mindfulness-based cognitive therapy for bipolar disorder: A systematic review and meta-analysis. (August 2020) - Xuan, Rongrong; Li, Xiaoming; Qiao, Yuxi; Guo, Qianhui; Liu, Xiaoyu; Deng, Wenrui; Hu, Qian; Wang, Kai; Zhang, Lei
Abstract: Background: Mindfulness-based cognitive therapy (MBCT) is an increasingly popular treatment for major depression and anxiety disorder, but has shown inconsistent efficacy for bipolar disorder (BD). Therefore, we conducted a meta-analysis to assess the general efficacy of MBCT for BD. Methods: Ten studies were identified that fulfilled the current inclusion criteria, including three controlled and seven uncontrolled studies. The effects of MBCT on depression, anxiety, mania, stress, mindfulness ability, and emotional regulation were assessed by comparing psychometric scale scores within groups (pre- vs. post-intervention) across trials as well as between groups (control vs. MBCT) across controlled trials. Results: Within-group comparison revealed a reduction in symptoms of depression ( g  = 0.37, 95%CI = 0.09−0.64, P  = 0.009) and anxiety ( g  = 0.45, 95%CI =0.16−0.75, P  = 0.002) following treatment compared to baseline. Stress symptoms were also significantly reduced ( g  = 0.39, 95%CI = 0.09−0.69, P  = 0.01), mindfulness ability ( g  = 0.63, 95%CI = 0.39−0.87, P <0.00001) and emotion regulation ( g  = 0.62, 95%CI=0.14−1.10, P  = 0.01) were significantly improved compared to baseline. However, symptoms of mania were not alleviated ( g =−0.26, 95%CI=−1.43−0.91, P  = 0.66). Subgroup analysis indicated that symptoms of depression and anxiety were still significantly improved at 3 months post-intervention ( g  = 0.46, 95%CI = 0.13−0.80, P  = 0.006 and g  = 0.57, 95%CI = 0.21−0.94, P  = 0.002, respectively) but not at 12 months ( g  = 0.04, 95%CI = −0.29−0.37, P  = 0.82 and g  = 0.17, 95%CI =−0.16−0.50, P  = 0.31). In between-groups analysis of controlled studies, MBCT significantly reduced depressive symptoms ( g  = 0.3, 95%CI =-0.05−0.65, P  = 0.09) but not anxiety symptoms ( g  = 0.51, 95%CI =  −0.20−1.22, P  = 0.16). Conclusion: Mindfulness-based cognitive therapy appears effective for alleviation of depression and anxiety among BD patients, possibly by improving emotional regulation and mindfulness abilities. However, efficacy appears time-limited and inconsistent, necessitating additional larger-scale studies and the development of post-intervention programs for sustained efficacy.